High-nickel ternary positive electrode material with surface coating, preparation method of high-nickel ternary positive electrode material and lithium ion battery
By constructing a CoTiO3 conductive coating on the surface of high nickel ternary positive electrode material and rapidly cooling, the problem of poor cyclic stability of high nickel positive electrode material under high Ni content is solved, and a high discharge specific capacity and good cyclic stability are achieved.
Patent Information
- Application Number
- CN202411728128.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to achieve good cycle stability of high nickel cathode materials while maintaining high discharge specific capacity. Especially when the Ni content exceeds 80%, there are problems such as irreversible phase change, cationic mixed discharge, surface alkali residuals, microcracks and gas production.
By introducing Ti source and Co source on the surface of high-nickel ternary positive electrode material, the CoTiO3 conductive coating is constructed in situ using high-temperature solid phase reaction, and rapidly cooled after sintering is completed to prevent further diffusing of Ti and Co elements into the crystal lattice.
The high ionic conductivity and discharge specific capacity of high nickel positive electrode materials are achieved, and the cycling stability is also good, which effectively suppresses the interface side reaction between the electrode material and the electrolyte, prevents surface erosion, and improves the rate performance of the material.
Smart Images

Figure CN119560529A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a high-nickel ternary positive electrode material with a surface coating, a preparation method thereof, and a lithium ion battery. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Lithium-ion batteries occupy the largest market share in rechargeable batteries due to their high energy density, excellent cycle life, no memory effect, safety and environmental protection. As one of the core materials of lithium-ion batteries, cathode materials play a vital role in the final performance of batteries. Compared with traditional cathode materials (such as layered structure cathode materials LiCoO2, spinel structure cathode materials LiMn2O4, olivine structure cathode materials LiFePO4), ternary cathode materials (LiNi x Co y Mn 1-x-y O2, LiNi x Co y Al 1-x-y O2) stands out among many positive electrode materials due to its high lithium desorption capacity and low cost advantages. However, with the increase of Ni content, especially when the Ni content exceeds 80%, it will cause a series of problems, such as irreversible phase change, cation mixing, surface residual alkali, microcracks, gas production, etc. during the cycle.
[0004] In order to solve the series of problems brought about by the increase of Ni content, surface coating is usually used to improve the performance of high-nickel positive electrode materials. However, there are many types of coating materials, and the selection of coating amount will have a great impact on the performance of the positive electrode material. Currently, there are few reports on the coating of high-nickel positive electrode materials with a Ni content higher than 80%, and the existing methods are difficult to simultaneously meet the requirements of high discharge capacity and long cycle stability. Therefore, how to provide a method for coating high-nickel positive electrode materials so that they can have good cycle stability while maintaining high discharge capacity when applied to lithium-ion batteries is an urgent problem to be solved. Summary of the Invention
[0005] In view of this, the present invention provides a high-nickel ternary positive electrode material with a surface coating, a preparation method thereof, and a lithium-ion battery. The high-nickel ternary positive electrode material with a surface coating provided by the present invention has good cycle stability when used and maintains a relatively high discharge specific capacity.
[0006] In a first aspect, the present invention provides a method for preparing a high-nickel ternary cathode material with a surface coating, comprising the following steps:
[0007] S1, the high nickel precursor Ni x Co y Mn 1-x-y (OH)2 is mixed with a lithium source and sintered to obtain a high-nickel lithium ion layered oxide; wherein 0.7≤x<1, 0<y<0.3;
[0008] S2. Dry-mixing the high-nickel lithium ion layered oxide with a titanium source and a cobalt source, and then sintering the mixture. After sintering, cooling the mixture at a rate of 15 to 30° C. / min to obtain the product.
[0009] Preferably, the high nickel precursor Ni x Co y Mn 1-x-y The ratio of the total molar amount of Ni, Co and Mn elements in (OH)2 to the molar amount of Li element in the lithium source is 1:(1.01~1.08).
[0010] Preferably, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate or lithium citrate.
[0011] Preferably, in step S1, the sintering temperature is 450-800° C., and the sintering time is 15-25 hours; and the sintering process is carried out in an oxygen-containing atmosphere.
[0012] Furthermore, the sintering process in step S1 is specifically as follows: heating to 450-550°C at a heating rate of 1-5°C / min and sintering for 3-8h; then heating to 600-800°C at a heating rate of 1-5°C / min and sintering for 10-20h.
[0013] Preferably, the titanium source is selected from TiO2, Ti(OH)4, TiCl4, C 12 H 28 O4Ti or TiC one or more; the cobalt source is selected from Co(OH)2, CoOOH, (CH3CO2)2Co, CoSO4, CoCO3 or Co3O4 one or more.
[0014] Preferably, the Ti content in the titanium source is 1500-2500 ppm, and the molar ratio of the Ti element to the Co element in the titanium source and the cobalt source is 1:(0.8-1.2).
[0015] Preferably, in step S2, the sintering temperature is 500-800°C, and the sintering time is 8-15 hours; the sintering process is carried out in an oxygen-containing atmosphere.
[0016] In a second aspect, the present invention provides a high-nickel ternary positive electrode material with a surface coating prepared by the above preparation method.
[0017] In a third aspect, the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the above-mentioned high-nickel ternary positive electrode material with a surface coating.
[0018] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0019] The present invention introduces a Ti source and a Co source on the surface of a high-nickel ternary cathode material. The Ti source and the Co source construct a CoTiO3 conductive coating in situ under a high-temperature solid-phase reaction. After sintering, the coating is rapidly cooled to avoid further diffusion of Ti and Co elements into the lattice, thereby avoiding capacity loss. CoTiO3, by virtue of its good thermal stability and electrical conductivity, can effectively inhibit the interface side reaction between the electrode material and the electrolyte, prevent surface erosion, and greatly improve the electrical conductivity of the material, reduce the charge transfer impedance during the cycle, and improve the rate performance of the material. When the high-nickel ternary cathode material with a surface coating provided by the present invention is applied to a lithium-ion battery, it has high ionic conductivity and discharge specific capacity, and has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings, which constitute part of the present invention, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute undue limitations thereon. It is obvious that one of ordinary skill in the art could derive other drawings based on these drawings without inventive effort.
[0021] Figure 1 This is a scanning electron microscope image of the high-nickel ternary cathode material with a surface coating according to Example 1 of the present invention;
[0022] Figure 2 1 is the first charge and discharge curve of Example 1 of the present invention and Comparative Example 1;
[0023] Figure 3 It is a comparison chart of the 1C & 50 cycle capacity retention rates of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0025] The present invention provides a method for preparing a high-nickel ternary positive electrode material with a surface coating, comprising the following steps:
[0026] S1, the high nickel precursor Ni x Co y Mn 1-x-y (OH)2 is mixed with a lithium source and sintered to obtain a high-nickel lithium ion layered oxide; wherein 0.7≤x<1, 0<y<0.3;
[0027] S2. Dry-mixing the high-nickel lithium ion layered oxide with a titanium source and a cobalt source, and then sintering the mixture. After sintering, cooling the mixture at a rate of 15 to 30° C. / min to obtain the product.
[0028] The present invention first prepares a high-nickel lithium-ion layered oxide, then dry-mixes it with a titanium source and a cobalt source, sintering it, and rapidly cooling it to obtain a high-nickel ternary positive electrode material with a CoTiO3 coating. The present invention adopts a dry mixing method to avoid the drying step of liquid phase mixing, making the preparation simpler and relatively lower in cost. The present invention performs a rapid cooling after the sintering step in step S2, which prevents the diffusion of Ti and Co elements into the inner layer, thereby avoiding capacity loss of the high-nickel positive electrode material.
[0029] The present invention utilizes titanium source and cobalt source to construct the CoTiO3 coating in situ. Compared with the scheme of directly mixing CoTiO3 with high-nickel lithium ion layered oxide, the interface between the coating constructed by the present invention and the high-nickel ternary positive electrode material is better compatible and has a tighter bonding. It is not easy to peel off during the cycle process, effectively protects the electrode material interface, and greatly increases the effect of improving performance such as cycle stability.
[0030] In the present invention, the high nickel precursor Ni x Co y Mn 1-x-y The ratio of the total molar amount of Ni, Co and Mn elements in (OH)2 to the molar amount of Li element in the lithium source is 1:(1.01~1.08), and more preferably 1:(1.03~1.07).
[0031] The present invention places no particular restrictions on the source of the high-nickel precursor; commercially available products can be used. The values of x and y are preferably within the range of 0.9 ≤ x < 1, 0 < y < 0.1. When the Ni content exceeds 90%, the resulting lithium-ion battery exhibits a higher specific discharge capacity, exceeding 200 mAh / g at 1C.
[0032] In the present invention, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate or lithium citrate; lithium hydroxide is preferred in the present invention, and lithium hydroxide monohydrate is more preferred for cost considerations.
[0033] In step S1 of the present invention, the sintering temperature is 450-800°C and the sintering time is 15-25h; the sintering process is carried out in an oxygen-containing atmosphere, and the LiNi x Co y Mn 1-x-y The volume fraction of oxygen in the oxygen-containing atmosphere is preferably above 80%, and more preferably a pure oxygen atmosphere.
[0034] The sintering process in step S1 of the present invention is specifically as follows: heating the material to 450-550°C at a heating rate of 1-5°C / min and sintering for 3-8 hours; then heating the material to 600-800°C at a heating rate of 1-5°C / min and sintering for 10-20 hours. This gradient heating method can pre-remove the crystal water in the raw materials and prevent the materials from being sintered too hard.
[0035] In the present invention, the titanium source is selected from TiO2, Ti(OH)4, TiCl4, C 12 H 28 O4Ti or TiC one or more; the cobalt source is selected from Co(OH)2, CoOOH, (CH3CO2)2Co, CoSO4, CoCO3 or Co3O4 one or more.
[0036] In the present invention, the titanium source has a Ti content of 1500 to 2500 ppm, specifically 1500 to 2500 ppm of the total mass of the titanium source, the cobalt source, and the high-nickel lithium ion layered oxide. The molar ratio of Ti to Co in the titanium source and the cobalt source is 1:(0.8 to 1.2).
[0037] The present invention does not impose any particular limitation on the dry mixing steps and equipment, and the dry mixing steps and equipment commonly used by those skilled in the art may be used.
[0038] In the present invention, in step S2, the sintering temperature is 500-800°C, more preferably 600-700°C; the sintering time is 8-15h; the sintering process is carried out in an oxygen-containing atmosphere, the volume fraction of oxygen in the oxygen-containing atmosphere is preferably above 80%, more preferably a pure oxygen atmosphere; the gas flow rate is 5-15L / min.
[0039] After the sintering step S2 of the present invention is completed, air cooling is used to quickly cool down the temperature. The present invention does not impose any special restrictions on this. Those skilled in the art can use conventional means to achieve the corresponding cooling rate.
[0040] The present invention also provides a high-nickel ternary cathode material with a surface coating, prepared by the aforementioned method. The surface of the high-nickel ternary cathode material is coated with an in-situ generated CoTiO3 coating. This coating effectively inhibits side reactions at the interface between the electrode material and the electrolyte, preventing surface erosion. It also significantly improves the material's electrical conductivity, reduces charge transfer resistance during cycling, and enhances the material's rate capability.
[0041] The present invention also provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the above-mentioned high-nickel ternary positive electrode material with a surface coating.
[0042] The present invention does not impose any particular restrictions on the preparation method of the lithium-ion battery, and a commonly used preparation method for lithium-ion batteries in the art can be used. The present invention preferably comprises: mixing the high-nickel ternary positive electrode material with a surface coating provided by the present invention, a conductive agent, a binder, and a solvent to obtain a positive electrode slurry; coating the positive electrode slurry on a positive electrode current collector to obtain a positive electrode sheet; and assembling the positive electrode sheet, an electrolyte, a separator, and a negative electrode sheet to obtain a lithium-ion battery.
[0043] The present invention does not impose any special restrictions on the selection of materials such as the conductive agent, binder, solvent, electrolyte, and separator, and any materials commonly used in the art may be used.
[0044] The technical solution of the present invention is further described below with reference to specific embodiments.
[0045] Example 1
[0046] This embodiment provides a method for preparing a high-nickel ternary positive electrode material with a surface coating.
[0047] (1) Weigh the commercial high nickel precursor Ni 0.93 Co 0.05 Mn 0.02 (OH)2 and lithium source LiOH·H2O, wherein the molar ratio of Li / (Ni+Co+Mn) is 1.05, are mixed uniformly with a high-speed mixer at a mixer speed of 500 r / min for 30 min to obtain a uniformly mixed mixture;
[0048] (2) sintering the mixture at high temperature in an oxygen atmosphere in a box-type atmosphere furnace, wherein the sintering steps are as follows: heating to 500°C at a heating rate of 2°C / min, sintering for 5 hours, then heating to 730°C, holding for 15 hours, and cooling to room temperature in the furnace after sintering to obtain a high-nickel lithium ion layered oxide;
[0049] (3) uniformly mixing the high nickel lithium ion layered oxide obtained in step (2) with TiO2 and Co(OH)2 (the molar ratio of Co element to Ti element is 1:1, and the Ti element content is 2000 ppm) using a high-speed mixing device (mixer speed is 500 r / min, mixing time is 30 min), and then heating to 650°C in a sintering device at a heating rate of 2°C / min, and sintering for 10 h in an oxygen atmosphere with an oxygen flow rate of 10 L / min;
[0050] (4) After sintering, the temperature is rapidly cooled at a rate of 20°C / min, and a high-nickel ternary positive electrode material with a surface coating is obtained.
[0051] The scanning electron microscope image of the high nickel ternary cathode material with surface coating prepared in this embodiment is as follows: Figure 1 As shown, it can be seen that the synthesized material is a large particle formed by the agglomeration of fine particles, with a rounded morphology, good particle size, and a particle size of about 10 μm.
[0052] Example 2
[0053] This embodiment provides a method for preparing a high-nickel ternary positive electrode material with a surface coating.
[0054] (1) Weigh the commercial high nickel precursor Ni 0.93 Co 0.05 Mn 0.02 (OH)2 and lithium source LiOH·H2O, wherein the molar ratio of Li / (Ni+Co+Mn) is 1.05, are mixed uniformly with a high-speed mixer at a mixer speed of 500 r / min for 30 min to obtain a uniformly mixed mixture;
[0055] (2) sintering the mixture at high temperature in an oxygen atmosphere in a box-type atmosphere furnace, wherein the sintering steps are as follows: heating to 500°C at a heating rate of 2°C / min, sintering for 5 hours, then heating to 730°C, holding for 15 hours, and cooling to room temperature in the furnace after sintering to obtain a high-nickel lithium ion layered oxide;
[0056] (3) uniformly mixing the high nickel lithium ion layered oxide obtained in step (2) with Ti(OH)4 and CoOOH (the molar ratio of Co element to Ti element is 1:1, and the Ti element content is 2000 ppm) using a high-speed mixing device (mixer speed is 500 r / min, mixing time is 30 min), and then heating to 650°C in a sintering device at a heating rate of 2°C / min, and sintering for 10 h in an oxygen atmosphere with an oxygen flow rate of 10 L / min;
[0057] (4) After sintering, the temperature is rapidly cooled at a rate of 20°C / min, and then a high-nickel ternary positive electrode material with a surface coating is obtained.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that the rapid cooling is not performed in step (4) of this comparative example. Step (4) of this comparative example is as follows:
[0060] After sintering, the material is cooled to room temperature in the furnace, and then a high-nickel ternary positive electrode material with a surface coating is obtained.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that steps (3) and (4) are not performed in this comparative example, and the high-nickel lithium ion layered oxide obtained in step (2) is directly used as the positive electrode material.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 1 is that in step (3) of this comparative example, the high nickel lithium ion layered oxide is directly mixed with the CoTiO3 compound. Step (3) of this comparative example is as follows:
[0065] The high nickel lithium ion layered oxide obtained in step (2) was uniformly mixed with the CoTiO3 compound (Ti element content was 2000 ppm) using a high-speed mixing device (mixer speed was 500 r / min, mixing time was 30 min), and then heated to 650°C in a sintering device at a heating rate of 2°C / min and sintered for 10 h.
[0066] Comparative Example 4
[0067] The difference between this comparative example and Example 1 is that in step (3) of this comparative example, Co(OH)2 is replaced by ZrO2, and the molar ratio of Zr element to Ti element is 1:1.
[0068] Comparative Example 5
[0069] The difference between this comparative example and Example 1 is that in step (3) of this comparative example, Co(OH)2 is replaced by MgO, and the molar ratio of Mg element to Ti element is 1:1.
[0070] Test example
[0071] Button Cell Preparation: The positive electrode materials prepared in the Examples and Comparative Examples were used in button cells for electrochemical performance testing. The battery assembly process was as follows: The positive electrode material, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed in a mass ratio of 8:1:1 and dissolved in N-methylpyrrolidone (NMP) to form a positive electrode slurry, ensuring that the slurry was free of particles. The slurry was evenly coated on aluminum foil using a coating machine to form a pole piece. The coated pole piece was placed in a vacuum drying oven at 120°C and dried for 12 hours. The pole piece was then removed and rolled on a roller press for later use. The electrode sheet was cut into 12mm diameter circular pieces using a cutting machine and dried in a vacuum drying oven at 60°C for 12 hours. The pieces were then removed and weighed using an electronic balance. Finally, the positive electrode sheet, lithium sheet, spring, gasket, positive electrode casing, negative electrode casing, polyethylene separator, and electrolyte were assembled into a CR2025 button-type half-cell in an argon-filled glove box. The electrolyte consisted of 1M NaPF₆ dissolved in a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC:DMC = 1:1 by volume). The metal lithium sheet served as the counter electrode. The charge and discharge voltage range was 2.75–4.3V, with an initial charge and discharge rate of 0.1C. The nominal specific capacity was 200mAh / g at 1C. Cycling performance was tested at a charge and discharge rate of 1C for 50 cycles.
[0072] The test results are shown in Table 1.
[0073] Table 1 Electrochemical performance test results of the assembled batteries of the embodiment and the comparative example
[0074]
[0075]
[0076] As can be seen from Table 1, the ionic conductivity of the positive electrode material after surface in-situ CoTiO3 modification is significantly improved, which is several orders of magnitude higher than that of the comparative example, which helps to improve the rate performance of the material. The positive electrode material after surface in-situ CoTiO3 modification shows a higher first discharge specific capacity than the comparative example. This is because during the sintering process, after rapid cooling, Ti and Co elements are enriched on the surface of the positive electrode material, preventing further diffusion into the lattice and avoiding capacity loss. In addition, the capacity retention rate of the modified positive electrode material after 1C&50 cycles is also higher than that of the comparative example. This is mainly because the stable CoTiO3 modification layer formed at the interface effectively inhibits the interface side reaction between the electrode and the electrolyte.
[0077] Figure 2 2 are the first charge and discharge curves of Example 1 and Comparative Example 1. It can be seen that the first discharge specific capacity of Example 1 is higher than that of Comparative Example 1. Figure 3This is a comparison chart of the 1C & 50-week cycle capacity retention rates of Example 1 and Comparative Example 1. It can be seen that although the battery cycle performance of Example 1 is significantly better than that of Comparative Example 1, this is mainly because Example 1 is rapidly cooled after sintering, and the Ti and Co elements are enriched on the surface of the positive electrode material, preventing further diffusion into the lattice, avoiding capacity loss, and the interface stability formed is better.
[0078] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-nickel ternary positive electrode material with a surface coating, characterized in that: The steps include: S1, high nickel precursor Ni x Co y Mn 1-x-y (OH)2 is mixed with a lithium source and sintered to obtain a high-nickel lithium ion layered oxide; wherein 0.7≤x<1, 0<y<0.3; S2, dry-mixing the high-nickel lithium ion layered oxide with a titanium source and a cobalt source, and then sintering the mixture. After sintering, cooling the mixture at a rate of 15 to 30° C. / min to obtain the mixture.
2. The preparation method according to claim 1, characterized in that The high nickel precursor Ni x Co y Mn 1-x-y The ratio of the total molar amount of Ni, Co and Mn elements in (OH)2 to the molar amount of Li element in the lithium source is 1:(1.01-1.08).
3. The preparation method according to claim 1, characterized in that: The lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate or lithium citrate.
4. The preparation method according to claim 1, characterized in that: In step S1, the sintering temperature is 450-800°C, and the sintering time is 15-25 hours; the sintering process is carried out in an oxygen-containing atmosphere.
5. The preparation method according to claim 4, characterized in that: The sintering process in step S1 is specifically as follows: heating to 450-550°C at a heating rate of 1-5°C / min, and sintering for 3-8h; then heating to 600-800°C at a heating rate of 1-5°C / min, and sintering for 10-20h.
6. The preparation method according to claim 1, characterized in that: The titanium source is selected from TiO2, Ti(OH)4, TiCl4, C 12 H 28 O4Ti or TiC one or more; the cobalt source is selected from Co(OH)2, CoOOH, (CH3CO2)2Co, CoSO4, CoCO3 or Co3O4 one or more.
7. The preparation method according to claim 1, characterized in that: The Ti content in the titanium source is 1500-2500 ppm, and the molar ratio of the Ti element to the Co element in the titanium source and the cobalt source is 1:(0.8-1.2).
8. The preparation method according to claim 1, characterized in that: In step S2, the sintering temperature is 500-800°C, and the sintering time is 8-15 hours; the sintering process is carried out in an oxygen-containing atmosphere.
9. A high-nickel ternary positive electrode material with a surface coating prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode comprises the high-nickel ternary positive electrode material with a surface coating as described in claim 9.
Citation Information
Cited By
Conductive network coating modified high-nickel ternary positive electrode material and preparation method thereof
CN121172122A
A conductive network coating modified high-nickel ternary cathode material and its preparation method
CN121172122B